Fisioterapia en la recuperación de las fracturas de Colles y Smith - Jara Bueno, Fabricio Vicente (2023)
ABSTRACT: The research was carried out through a bibliographic review collecting scientific articles from the year 2013 onwards with the theme "Physiotherapy in the recovery of Colles and Smith fractures", 35 scientific articles suitable for research were chosen, which were extracted from different scientific databases such as: ProQuest, PubMed, Google Scholar and Scopus The type of research that is presented is documentary using information from printed materials such as scientific articles, books, magazines and sometimes documents from web pages that were previously analyzed, which led to obtaining a better result. There are different mechanisms of production of trauma in forearm fractures, we will focus on two of them, the Colles Fracture and the Smith Fracture. Colles' fracture is the most frequent, it is produced by a fall with the wrist extended. It is an extra-articular fracture where the distal fragment has a dorso-radial displacement with a certain degree of supination. The extra-articular inverted Smith or Colles Fracture that occurs as a consequence of a fall with the wrist in flexion, the distal fragment displaces to the volar aspect of the radius. The investigation of the health problem seeks to reflect the need to apply appropriate protocols for proper management of physiotherapy in Colles and Smith fractures, because there is not much information in our country on the subject.